Business Feasibility Analysis, Reviewed From Marketing Aspects, Financial Aspects, Accounting Knowledge, And Business Experience Towards The Use Of Accounting Information In Micro, Small And Medium Enterprises In Jambi City - Erma Yani; Afrizal Afrizal; Yuliusman Yuliusman (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of marketing aspects, financial aspects, accounting knowledge, and business experience on the use of accounting information in Micro, Small, and Medium Enterprises in Jambi City. A quantitative approach was used, with data collected through questionnaires from 100 owners. The analysis was conducted using Partial Least Squares (PLS). The results indicate that accounting knowledge and financial aspects have a significant effect on the use of accounting information, while marketing aspects and business experience do not show a significant effect. These findings highlight the importance of accounting knowledge and sound financial management in supporting accounting-based decision-making in.